Lettering, Darabshaw House - Ghosh, Ayan (2023)
The Darabshaw family has been involved in the shipping business since the early 19th century. Its founder, Darabshaw B. Dubash, established DBC and Sons (Gujarat) Private Limited in 1929 for operations as stevedores, ship agents, ship chandlers, and landing and shipping contractors. It is now run by the seventh generation of the Dubash family.